Uncovering the Debate of Nature and Nurture about Evil in Lord of the Flies through Diction - Aziz, Inzamam (Pakistan Languages and Humanities Review, 2024)
The purpose of this study was to find out whether the violent behavior of human beings is the product of their nature, or it is the nurture or atmosphere that forces them to engage in evil acts. Earlier on, this contrast had been touched by psychologists, philosophers, and researchers, but no one has explored this concept in Golding’s use of diction in “Lord of the Flies." Through qualitative research methods, I have tried to explore the diction used by William Golding in his novel Lord of the Flies, in which he depicts that evil is in the nature of man, but civilization has masked it. When free from societal constraints, humans’ natural impulse towards evil emerges, causing them to behave like beasts. These findings may help future researchers to delve deeper into understanding how different aspects of nurture, such as upbringing and social environment, impact the inherent evil nature of individuals.